Assistência pré-natal em época de pandemia Covid-19 em região da faixa de fronteira - Fernández, Pamela Aracely Ayala (2023)
The COVID-19 pandemic represented one of the biggest global health challenges of this century, and the impact generated is related to the growth in hospitalization and mortality rates due to the disease. This study aimed to analyze prenatal care in times of COVID-19 in the 9th and 10th Health Regions of the State of Paraná. This is a comparative study, with a cross-sectional and retrospective design, applying a quantitative approach. The tool used was a closed questionnaire, with interviews carried out at Hospital Ministro Costa Cavalcanti and at the university hospital of Universidade Estadual do Oeste do Paraná, in the year 2021. For data analysis, the level of significance adopted was 5%, and the IBM SPSS Statistics program, version 19 for Windows, was used. A total of 804 women were interviewed in the two health regions. The predominant age group was 21 to 40 years old (82.0%), Caucasian (56.0%) and with more than 9 years of education (86.0%); many pregnant women developed illnesses during the pandemic period (55.9%), some tested positive for COVID-19 (16.0%), mainly in the third trimester of pregnancy (39.7%), others needed specialist care (33 .1%) and suffered complications during pregnancy (34.7%). Regarding the number of appointments, the average in the health regions was around 10 appointments; concerning risk classification, the highest frequency was usual risk pregnancies (56.0%), with the primary healthcare unit standing out as the place for prenatal care (72.9%). Pregnant women underwent rapid tests for Sexually Transmitted Infections, showing good adherence and availability for detecting these diseases; the COVID-19 vaccine had low acceptance (80.1%), and the established COVID-19 measures in the health regions were successful. This study found that, despite all the complications related to COVID-19, maternal and child healthcare was provided satisfactorily.